Confusion and Ataxia in a Middle Age Woman: A Case with Four Diagnoses Discussed at the Edinburgh Advanced Clinical Neurology Course in 2001. Issue 5 (1st October 2003) - Williams, Anna; Fuller, Geraint; Bell, Jeanne E.; Warlow, Charles P.
Abstract : THE CLINICAL STORY In April 2000, a lady in her early fifties presented with a two-week history of gradually increasing confusion, poor memory, an unsteady gait, and intermittent nausea and vomiting. On the day of consultation, she also developed a mild occipital headache. In 1980, she had been diagnosed with breast cancer (T1N0M0) for which she had had a right mastectomy and radiotherapy. She had been intermittently treated for depression and pain in the right arm since then. She was taking regular paroxetine and amitriptyline, bendrofluazide for lymphoedema, and hormone replacement therapy. She was an ex-smoker of 10 years, and drank four units of alcohol a day. She lived with her husband. Family history was unremarkable. She was admitted to a local hospital, and transferred to the neurology department in Edinburgh four days later on the 28 April 2000. EXAMINATION She was agitated and confused, being orientated in time only.